HOT SPOTS OF MANTLE AND EXPERIMENT TO 10 GPA: ALKALINE REACTIONS, LITHOSPHERE CARBONATIZATION, AND NEW DIAMOND-GENERATING SYSTEMS - Litvin Yu.A. (My University, 1998)
The peculiarities of the interaction of chemically active alkaline-fluid plume components with major minerals of the lithosphere (the situation of hot spots of mantle) were experimentally studied at a pressure as high as 10 GPa. Active interaction of model alkaline-carbonate component K2CO3 with forsterite and enstatite results in formation of carbonates Mg2CO3 and K2Mg(CO3)2. At 3.7 GPa, the phase equilibria of the forsterite - K2CO3-K2SiO3 system are represented by periclase- and forsterite-bearing subsolidus mineral associations with participation of MgCO3, K2Mg(CO3)2, and K2CO3. These facts may point to intense carbonatization of the lithosphere. At pressure above 4.0 GPa, alkaline reactions of aluminosilicate plume components NaAlSi2O6 (jadeite) and NaAlSiO4 (nepheline) with forsterite and enstatite give rise to silicate Na2Mg2Si2O7 (which may be a new mantle mineral) and pyropic garnet Mg3Al2Si3O12. The phase equilibrium in the forsterite-jadeite and enstatite-nepheline pseudobinary systems on their melting at 6 GPa are controlled by invariant peritectics. High-pressure interaction of alkaline-carbonate plume components with forsterite results in formation of a series of carbonates with mixed Na, K, and Mg cations. The carbonate melts were tested as media for diamond crystallization. The experiments at 8-10 GPa have shown that diamond efficiently crystallizes in the carbonate-carbon melts of the Na2Mg(CO3)2-K2Mg(CO 3)2-C (graphite) system in the cases of both spontaneous and seed-stimulated kinds of nucleation.